Collaboration relationship between university and software industry based on knowledge management: an exploratory approach - Chedid, Marcello Fernandes (2019)
The current environment that characterizes the software industry is extremely dynamic and somewhat complex demanding high-performance solutions, rapid development and cost efficiency. The collaboration relationship with universities has been represented a key resource, to the extent that together more easily can promote technological development that underpins innovation solutions. In addition, several studies point out knowledge sharing as an important and strongly influential factor in a collaboration relationship. In this context, the present thesis aims to identify a set of factors that can enhance and/or facilitate the collaboration relationship between the university and the software industry in a sustainable way, based on knowledge management. In line with the general objective three research questions were defined: (i) What are the main motivations that lead to the decision of establishing a collaboration relationship?; (ii) What are the management mechanisms used in the governance of collaboration relationships?; (iii) What are the principles and culture of knowledge management and of knowledge sharing in these organizations? In order to answer those questions and, consequently, achieve the general objective, an initial quantitative study based on a questionnaire was conducted. This study aims to explore and understand the practice of knowledge sharing and collaboration in the context of a university. Overall it was concluded that, knowledge sharing positively affects the collaboration behavior. The obtained results also showed that in order to promote and encourage knowledge sharing and, consequently, to foster collaboration relationships, it is important to work mechanisms based on intrinsic motivation and networking. Subsequently, it was conducted a qualitative study based on interviews in order to identify a set of factors that could enhance/facilitate the collaboration relationship between the university and the software industry in a sustainable way, based on knowledge management. Participants with complementary visions and different experiences in the two types of involved industries and simultaneously, with decisionmaking positions were interviewed. The results revealed that collaboration relationships established among these organizations are set-up only as a ‘connection’. This ‘connection’ is characterized by being a simple exchange, without building a sustainable collaboration relationship; although, those involved point to advantages in the existence of a sustainable collaboration relationship. The results also revealed that the collaboration relationships are usually conducted through informal communication channels, which makes it difficult to capture and disseminate knowledge to other remaining members of each involved organizations. In nutshell and in practical terms, this work contributes to the identification and analysis of a set of factors that enhance a collaboration relationship between university and software industry. This result can support organizations in the strategies definition for the development of actions, in order to promote a sustainable collaboration relationship. In theoretical terms, this work contributes to the increase of the body of knowledge in the area, with empirical results, since the literature point the lack of empirical studies as the main gap in this area of knowledge.